2022
DOI: 10.3390/cancers14051138
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Epithelial-to-Mesenchymal Transition (EMT) from Bench to Bedside

Abstract: The epithelial-to-mesenchymal transition (EMT) and its reversal, the mesenchymal-to-epithelial transition (MET) are critical components of the metastatic cascade in breast cancer and many other solid tumor types. Recent work has uncovered the presence of a variety of states encompassed within the EMT spectrum, each of which may play unique roles or work collectively to impact tumor progression. However, defining EMT status is not routinely carried out to determine patient prognosis or dictate therapeutic decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Analysis of human cancer datasets also demonstrated that the EMT score (based on different EMT signatures) [ 94 ] strongly correlated with the immunosuppression signatures across different types of solid cancers [ 95 98 ]. The EMT score was found to be inversely associated with CD8 + T-cell infiltration in lung cancer [ 82 , 96 ].…”
Section: Advanced Methods To Study Icb Response Of Emp: Are Mesenchym...mentioning
confidence: 99%
“…Analysis of human cancer datasets also demonstrated that the EMT score (based on different EMT signatures) [ 94 ] strongly correlated with the immunosuppression signatures across different types of solid cancers [ 95 98 ]. The EMT score was found to be inversely associated with CD8 + T-cell infiltration in lung cancer [ 82 , 96 ].…”
Section: Advanced Methods To Study Icb Response Of Emp: Are Mesenchym...mentioning
confidence: 99%
“…The initiation of EMT was featured by the downregulation of epithelial markers (i.e., E-cadherin) and the upregulation of mesenchymal markers (i.e., N-cadherin and Vimentin, etc.) [32]. In summary, circCRIM1 functioned as an onco-circRNA in ESCC cells by promoting proliferation, colony formation, migration, invasion, and EMT.…”
Section: Discussionmentioning
confidence: 93%
“…In in vitro systems, the state of EMT can be assessed using established markers that span a range of characteristics, from indicators of cellular stemness to markers of morphological alterations and transcriptional regulators. 34 For instance, the analysis of E-cadherin (an epithelial marker) and vimentin (a mesenchymal marker) at the transcriptional level or through immunofluorescent microscopy has been extensively utilized in traditional 2D platforms, 34 as well as in MPSs. [35][36][37]…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%